1994
DOI: 10.1093/infdis/170.6.1616
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology Of Chronic Pseudomonas aeruginosa Infections In Cystic Fibrosis

Abstract: The epidemiology of chronic colonization of airways with Pseudomonas aeruginosa was monitored in 44 patients with cystic fibrosis (CF) by DraI/SpeI macrorestriction analyses of 489 isolates. Sequential P. aeruginosa isolates (144) that had been collected from 32 CF patients over < or = 2.5 years were investigated, and 12 patients were followed for 8 years after onset of colonization. Forty-eight different genotypes were uncovered from 481 typeable isolates. Ten genotypes were found in > 1 unrelated CF patient.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
203
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(224 citation statements)
references
References 9 publications
16
203
1
4
Order By: Relevance
“…Therefore, strains of this group may also have emerged from the environment. This is in accordance with the conclusion of another European study, which found that 28 % of CF isolates were related to 21 % of P. aeruginosa isolates from an aquatic habitat (Romling et al, 1994).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, strains of this group may also have emerged from the environment. This is in accordance with the conclusion of another European study, which found that 28 % of CF isolates were related to 21 % of P. aeruginosa isolates from an aquatic habitat (Romling et al, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the gene was probably acquired by horizontal transfer, as observed previously for some other bacterial sialidase genes (Roggentin et al, 1993). The prevalence of nan1 in plant strains, the stability of the genotype of P. aeruginosa isolates from the pulmonary tract of CF patients (Romling et al, 1994;Renders et al, 1996) and the strong correlation between RAPD and MLEE results suggest that such genetic events probably originated in environmental populations of strains rather than in CF populations.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…32 The most relevant result of our study is the fi nding that four main bacterium clusters, with the predominance of two clusters, are responsible for colonizing CF patients. This suggests that either there is a strong selection towards a specifi c genotype, which could originate by chromosome rearrangements, 33,34 or that primarily specifi c isolates containing pathogenic gene islands may be responsible for the initial and subsequent colonization processes. As this study was carried out using a small number of patientes and strains this statement cannot be generalized for all cystic fi brosis population and further studies must be accomplished to confi rm it.…”
Section: Discussionmentioning
confidence: 99%